Treatment pathways and rebound-rate of prehospital viral croup attacks—data from a prehospital pediatric physician led emergency service—a prospective observational follow-up study - Hey, Florian; Lieftüchter, Victoria; Olivieri, Martin; Zimatschek, Sebastian; Hoffmann, Florian; Pfeiffer, Daniel (Frontiers in Pediatrics, 2025)
IntroductionRespiratory illnesses, often caused by upper or lower airway obstruction, represent one of the most common pediatric emergencies. Croup syndrome is the most frequent cause of inspiratory stridor. The study aims to record the incidence, current treatment, and further care measures. Additionally feasibility and suitability of future telemedical consultations for pseudo-croup syndrome should be evaluated.MethodsA prospective observational follow-up study of children aged 0–18 years who were seen by the Munich physician-led prehospital pediatric emergency service from October 15, 2020 to April 30, 2023. The attending emergency physician completed an anonymous questionnaire with treatment information. The child's parents provided a second questionnaire regarding the clinical course and further care in the 12 h following the initial presentation.ResultsA total of 226 patients, 154 (68.1%) with a corresponding parental questionnaire, were analysed. The average age was 3.4 years (range 5 months to 9.5 years), with most patients in the toddler (37.6%; n = 85) and early childhood (45.1%, n = 102) age brackets. 8.4% (n = 19) of patients had a, most frequently respiratory (52.6%, n = 10), chronic precondition. The average Westley Score in our cohort was 4.1. Every year increase in age reduces the average Westley score by 21.2% (p = 0.034). Acute therapy consists of steroids rectally (98.2%, n = 222), adrenaline (85.8%, n = 194) and cold/fresh air (78.8%, n = 178) inhalations. 39.8% (n = 90) of patients were transported to the hospital, and a physician accompanied a third (35.6%, n = 32). The strongest predictor for the necessity of physician-accompanied transport was prolonged adrenaline inhalations (OR: 11.25). Nearly ¾ of patients (70.2%, n = 47) were discharged from the emergency department. Of all admitted patients (n = 20), 10% (n = 2) needed intensive care. Out of all patients (n = 226), in 7% (n = 10) of cases with parental information on reoccurrence, a reoccurrence of the croup attack within 12 h was reported.Conclusion(s)Croup syndrome attacks have a low risk of hospitalisation and rebound. In light of increasingly limited healthcare resources, this study identifies several significant influencing variables for the treatment pathways and proposes a potential treatment algorithm. No patient needed invasive treatments, rendering croup attacks in children a possible target for telemedical consultations with no necessity for on-site physician presence.